Process modelling, design and technoeconomic Liquid–Liquid Extraction (LLE) optimisation for comparative evaluation of batch vs. continuous pharmaceutical manufacturing of atropine - Diab, Samir; Mytis, Nikolaos; Boudouvis, Andreas G.; Gerogiorgis, Dimitrios I. (Computers & chemical engineering, 2019)
•Upstream plantwide modelling and optimisation of the continuous pharmaceutical manufacturing (CPM) of atropine.•Continuous liquid–liquid extraction (CPM-LLE) design considers ternary phase composition modelling (UNIFAC) and estimated solute partitioning between product LLE phases.•Technoeconomic optimisation for comparative evaluation of separation solvents for CPM-LLE under varying design assumptions (plant capacity, solvent recovery).•Toluene emerges as the most economically viable CPM-LLE solvent choice compared to the batch LLE designs, followed by diethyl ether and n-butyl acetate.•Toluene usage allows acceptable E-factors for pharmaceutical processes. Continuous Pharmaceutical Manufacturing (CPM) can revolutionise industrial efficiency via potential operational and economic benefits over currently dominant batch methods. Process modelling and optimisation are valuable towards rapid design space evaluation and elucidation of optimal process design configurations, without expensive and time-consuming experimental campaigns. This paper pursues total cost minimisation via nonlinear optimisation of different separation design options for atropine, a product of great societal importance. The study considers a demonstrated continuous flow synthesis, presents reaction kinetic parameter estimation towards reactor design, and illustrates a comparative analysis of the subsequent batch vs. continuous liquid–liquid extraction (LLE) for product purification, using published partition coefficient data and UNIFAC-modelled ternary liquid–liquid equilibria. Original optimisation results show that toluene is the best continuous LLE solvent, attaining the lowest total costs at both plant capacities considered and the greatest total cost savings with respect to the batch LLE design for varying solvent recovery, at acceptable material efficiencies.